THE EFFECT OF COMMUNITY LANGUAGE LEARNING (CLL) TOWARD STUDENTS SPEAKING ABILITY FOR THE ELEVEN GRADE STUDENT OF SMK TELADAN BATAM - Winda Evyanto (Universitas Putera Batam, 2015)
Many students in Indonesia do not like English. They get difficulties, boredom and confusing in learning it. English teacher should be able to motivate the learners in learning this foreign language. Harmer (1993: 3) states motivation means a kind of drive that encourages somebody to pursue a course action. It should be done by every English teacher in order that the students are interested to learn this language. English teacher must be able to manage the teaching by using certain method in the teaching-learning process, so that the students will like it without boring and despair. Community Language Learning (CLL) as one kind of method in language learning, “The learners become members of a community – their fellow learners and the teacher to learn through interaction with members of the community. Learning is not viewed as an individual accomplishment but as something that is achieved collaboratively. Learners are expected to listen attentively to the teacher, to freely provide meanings they wish to express, to repeat target utterance without hesitation, to support fellow members of the community